Reforma tributária: prisma constitucional das propostas de unificação dos tributos sobre o consumo (IPI, PIS, COFINS, ICMS E ISS) no direito Brasileiro - uma análise acerca da (in)constitucionalidade das propostas de reforma tributária tendentes a implementação de IVA unificador dos tributos sobre o consumo - Silva, Marcos Danilo Barreto da (2023)
The present work aims to identify and elucidate the constitutional contours and/or unconstitutional aspects of tax reform proposals aimed at implementing a unified VAT on consumption taxes (PEC 49/2019, PEC 110/2019). To achieve this, a critical and analytical view of the constitutional prism of such proposals will be established in relation to the system, particularly with respect to the principle of federalism. This work focuses on the public law, specifically in the field of taxation, addressing the structural archetype of the federal state. Concepts and premises established by leading thinkers in the field will be used in a detailed approach to the controversies surrounding the subject matter, including the issue involving the prohibition of alteration of the federal state provided for in Articles 1 and 18 of the Brazilian Federal Constitution of 1988, which have the status of a constitutional clause (Article 60, § 4, I, CRFB/88). Additionally, this work examines the possibility of reorganizing the National Tax System to simplify taxation and thus promote to relieving of the production chain